HEALTH RISK ASSESSMENT OF METAL CONTENT IN TUMERIC (Curcuma longa) CULTIVATED IN MARO FARMLANDS KAJURU LGA, KADUNA STATE, NIGERIA - Allems, Godwin Asoconom; Uduma, A. U.; Okonola, O. J. (FUDMA JOURNAL OF SCIENCES, 2022)
Turmeric powder (Curcuma longa) is a yellow powder obtained by grinding dried matured rhizomes. Curcuma longa is utilized in culinary and cosmetic preparations, as well as medicinal formulations. It’s available in Kajuru LGA, Kaduna state, Nigeria’s Maro ward. The purpose of this study was to carry out a health risk assessment of Na, Mg, K, Ca, and Fe metals in turmeric cultivated within Maro, Chibiya, Karamai, and Angwan Gamu farm lands. Using the Perkin Elmer pin AAcle 900H, four Curcuma longa samples were obtained from diverse fields and subjected to AAS analysis following wet digestion to assess metal contents. The data was examined statistically using analysis of variance (ANOVA). Ca>Mg>Na>K>Fe were found to be the most abundant metals in Curcuma longa. The maximum level advised by the World Health Organization for all elements was not exceeded (WHO). At P>0.05, there were substantial differences in metal content in Tumeric across all farmlands. Consumers of Curcuma longa cultivated in Maro will not be exposed to any potential health problems because the Target Hazard Quotient (THQ) value of all metals was less than one and the Hazard Index (HI) value for Fe metal was less than one. It was suggested that more research be done on the health risks of other metal content in Curcuma longa rhizome.